Asymmetric pitx2 expression in medaka epithalamus is regulated by nodal signaling through an intronic enhancer - Soukup, Vladimir; Mrstakova, Simona; Kozmik, Zbynek (Development genes and evolution, 2018)
The epithalamic region of fishes shows prominent left-right asymmetries that are executed by nodal signaling upstream of the asymmetry-determining transcription factor pitx2. Previous reports have identified that nodal controls the left-sided pitx2 expression in the lateral plate mesoderm through an enhancer present in the last intron of this gene. However, whether similar regulation occurs also in the case of epithalamic asymmetry is currently unresolved. Here, we address some of the cis-regulatory information that control asymmetric pitx2 expression in epithalamus by presenting a Tg(pitx2:EGFP) 116-17 transgenic medaka model, which expresses enhanced green fluorescent protein (EGFP) under control of an intronic enhancer. We show that this transgene recapitulates epithalamic expression of the endogenous pitx2 and that it responds to nodal signaling inhibition. Further, we identify that three foxh1-binding sites present in this enhancer modulate expression of the transgene and that the second site is absolutely necessary for the left-sided epithalamic expression while the other two sites may have subtler regulative roles. We provide evidence that left-sided epithalamic pitx2 expression is controlled through an enhancer present in the last intron of this gene and that the regulatory logic underlying asymmetric pitx2 expression is shared between epithalamic and lateral plate mesoderm regions.
Keywords: funkční lateralita; Oryzias; Functional Laterality; forkhead transkripční faktory; vývojová regulace genové exprese; transkripční faktory; Mesoderm; Enhancer; zvířata; Embryo, Nonmammalian; embryo nesavčí; zelené fluorescenční proteiny; Transgenes; protein nodal; homeoboxový protein PITX2; Introns; Signal Transduction; Transgene; epitalamus; Enhancer Elements, Genetic; pitx2; Binding Sites; signální transdukce; Asymmetry; Medaka; zesilovače transkripce; Homeodomain Proteins; transgeny; Epithalamus; introny; Animals; Forkhead Transcription Factors; homeodoménové proteiny; Green Fluorescent Proteins; vazebná místa; Nodal Protein; Transcription Factors; Gene Expression Regulation, Developmental; Homeobox Protein PITX2; mezoderm